Perlindungan Hukum Pada Orang Tua (Kajian Norma Hukum Dan Norma Agama) - Tomy Michael (STIH Zainul Hasan Kraksaan Kraksaan, 2026)
In the concept of a state of law, the legal subject is a protected party. The existence of legal subjects in national law and international law has significant differences. In the perspective of national law, legal subjects are everything that can have rights and obligations according to law or all supporters of rights and obligations according to law. The research method uses normative legal research with a statutory regulatory approach. In the end, parents must receive important attention from the state. The existence of children is very important, but in forming children is a special relationship between parents and children